Determinants of the severity of sports injuries among students in sports disciplines at higher education institutions - Mingxi Li; Mingxi Li; Junwei Wang; Jisheng Xu; Yi Jia (Frontiers in Public Health)
IntroductionThis study aims to analyze and identify the main factors influencing the severity of sports injuries among university sports students.MethodsThe study involved students aged18.5 to22.2 years from five sports programs in Sichuan Province. Data were gathered via online questionnaires and interviews in February-March2024, assessing personal characteristics and fitness indicators, with binary logistic regression applied to analyze injury severity.ResultsA total of 1,190 valid responses were collected, comprising 837 males and 353 females. Univariate analysis showed that BMI, time of day, temperature perception, adherence to technique, warm-up activities, physiological condition, training duration, and vital capacity were statistically significant. Binary logistic regression analysis indicated. Factors significantly associated with increased severity of sports injuries included body mass index (BMI) categorized as underweight or overweight (OR = 1.761, p = 0.001), afternoon training sessions (OR = 1.499, p = 0.012), evening training sessions (OR = 1.888, p = 0.003), presence of illness or injury (OR = 1.785, p = 0.004), training duration of 12 h or more per week (OR = 1.355, p = 0.047) were positively correlated with the occurrence of severe sports injuries, and minimal warm-up activities (OR = 0.701, p = 0.015) was negatively correlated with the occurrence of severe sports injuries.ConclusionBMI, training time, physiological state, weekly training duration, and warm-up practices significantly affect sports injury severity. Educational institutions should develop informed strategies in academic and training programs to reduce injury severity and ensure student health and safety.